Placebo and nocebo in analgesia - psychiatric aspects - Latas, Milan (Engrami, 2022)
The paper presents the placebo and nocebo effects that occur in analgesia with a review of way how to recognize them in clinical practice and with the presentation of some psychological and psychiatric elements of the placebo and nocebo effects in clinical practice. The definition of placebo in analgesia implies the reduction of pain due to the use of an inert substance with the information that the substance effectively relieves pain. For now, the mechanism of action of placebo is not completely clear, even in analgesia, but based on numerous studies and extensive clinical experience, it is assumed that there are certain psychological and psychiatric factors that are associated with the placebo effect. On the other hand, the nocebo effect represents the ability of negative beliefs and expectations that cause harm/a negative effect in the body. Thus, nocebo represents the effect of negative expectations from treatment. Unfortunately, there was no research that would indicate the psychological / psychiatric mechanisms of the nocebo effect i clinical practice. Overall, based on extensive experience and based on a number of studies that have been done, it can be concluded that both placebo and nocebo meet in everyday medical practice. How intense it will be depends on many factors. That is why it is important to properly recognize and control them when working with patients. Further research may have profound implications for understanding these phenomena.
Keywords: Placebo, nocebo, psychiatry, analgesia